KAJIAN PENGETAHUAN LOKAL MASYARAKAT PETANI DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI (DAS) KETAHUN DI KABUPATEN LEBONG - Purwoko, Agus; Sukiyono, Ketut; Cahyadinata, Indra (Jurnal AGRISEP, 2017)
The research are aimed at exploring farmers’ local knowledges on upstream of Ketahun Watershed area (Lebong District) to manage natural resources (forest, wet rice field, and plantation field). An analytical descriptive method is used analyze data gathered from interview to 80 farmers selected by purposive sampling. The reserach indicates that sources of farmers’ local knowledge on natural resources management come from internal and external social system. Farmers’ local knowledge can be analyzed by description of pragmatic and supranatural local knowledges. Characteristics of pragmatic local knowledges among others (1) reforestation, (2) social participation to guard forest function, (3) conservation of forest by durian fruit, tree similar to jackfruit and tree that produces beans with pungent odor, (4) applicaton of green revolution although has not yet appropriate with the package of technology recommendation, (5) maintaining of planting inserted, (6) maintaining of agroforestry on plantation area, and (7) perpetuating trees all along rivers. While, characteristics of supranatural local knowledges such as: (1) prohibited to spit, to urinate, to speak any old, fell of trees, and to take firewood on the areas that are consider sacred, (2) ngepoa means the process of good forest burn, (3) kiyeu setimbang alam means trees on along of watershed that prohibited to fell, and (4) mundang biniak means ritual of rice planting season for honoring Dewi Sri until rice plants can grow rapidly and can produce rice highly. Implication of the research are (1) involvement of local institutions to help farmers for maintaining natural resources based on local knowledges adn (2) increasing of farmers ability to select agricultural innovation for sustainability of natural resources.